ANALISIS DIGITAL FORENSIK REKAYASA IMAGE MENGGUNAKAN JPEGSNOOP DAN FORENSICALLY BETA - Irwansyah Irwansyah; Helda Yudiastuti (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
The development of information technology is not only beneficial for humans, but often also used for negative purposes. Crime by utilizing digital image technology is very easy to do using a computer, so it is not surprising if more and more cases of cybercrime occur. The spread of digital images on social media in the form of images or videos raises public anxiety that these images or videos cannot be considered reliable evidence, because both images and videos can be easily engineered. The purpose of this study is to analyze a digital image that has been manipulated or engineered using a particular software or program. Image manipulation techniques that will be used are: Image splicing, copy-move, and retouching images. While the analysis tool uses the ELA method introduced by Krawetz which is available online from the website (https://29a.ch/photo-forensics/#forensic-magnifier) ​​and Jpegsnoop software.